Laboratory static hardness tests of metals - Ng, Jona Rui Qi (Nanyang Technological University, 2022)
The aim of Laboratory Static Hardness Tests of metals is to perform mechanical testing to determine the hardness value of the available alloys. This report will focus on the theory and experiment on how hardness value is determined through the means of Vickers hardness testing as per American Society for Testing and Materials (ASTM) testing standards and guidelines. Having done the Vickers hardness experiment, we will be able to achieve the Vickers hardness value. With the value, the report will further provide other different kinds of hardness value using the conversion table as per ASTM standards.